Pengembangan Media Pop-Up Book “Eksotika” pada Materi Kearifan Lokal untuk Siswa Kelas IV di UPT SDN 256 Gresik - Nailatul Karimah; Iqnatia Alfiansyah; Nataria Wahyuning Subayani (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimed to describe: (1) the development process of the Eksotika Pop-Up Book media on local wisdom material for fourth-grade elementary school students, (2) the validity of the media, (3) its effectiveness, and (4) students’ responses toward the media. This research employed a Research and Development (R&D) method using the ADDIE model, consisting of Analyze, Design, Development, Implementation, and Evaluation stages. The study was conducted at UPT SDN 256 Gresik. Data were collected through interviews, observations, validation questionnaires from media and material experts, student response questionnaires, and learning outcome tests. The results showed that the Eksotika Pop-Up Book media was feasible for use in learning activities, obtaining a media expert validation score of 95.31% and a material expert validation score of 93.75%, both categorized as very valid. The media and content were aligned with the learning objectives and supported students’ understanding of local wisdom traditions in Gresik, including Rebo Wekasan, Malam Selawe, Pasar Bandeng, Sanggring, Pencak Macan, and Damar Kurung. Therefore, the Eksotika Pop-Up Book is considered valid and feasible as an alternative learning medium for Grade IV IPAS learning.